Multi-Disciplinary Characteristics of Double-Skin Facades for Computational Modeling Perspective and Practical Design Considerations - Memari, Ali M.; Solnosky, Ryan; Hu, Chengcong (Buildings (Basel), 2022)
Vertical building enclosures known as Double-skin façades (DSFs) have become recognized as a promising façade type for buildings that place emphasis on sustainable, green, and energy-efficient design performance. DSFs are highly integrated across engineering and architecture; however, there remain limited centralized knowledge repositories that offer designers’ insight into these performance trends, multi-disciplinary collaboration, and tradeoff metrics, as well as how to go about modeling DSFs for performance under applicable loading systems when conducting design. As such, the main objective of this paper is to provide a better understanding of different types of DSF systems and their attributes from the perspective of multiple disciplines, as well as different modeling approaches. The methodology adopted is rooted in the principles of systematic literature review of design standards, research papers, and software manual literature, as well as a qualitative evaluation based on structural performance aspects. From the study, many different configurations of DSFs exist that impact each engineered system, where those system attributes impact multiple systems. This results in a need to parametrically iterate configurations within software to find a balance in DSF performance. Furthermore, there exists software easily capable of simulating these systems, yet the designer must carefully construct the models with different levels of sophistication towards DSFs and the software. This paper contains concise summaries of key attributes that designers need to consider when their project has a DSF system, along with different software modelers from which they can choose, correlating to the complexity of the design stage along with the appropriateness of the calculations.